Histomorphological study of gastric mucosal biopsy in dyspepetic patients and its association with Helicobacter pylori infection - Prachi,; M Shanthi,; Kasa Somsekhar, (Eastern Journal of Medical Sciences, 2020)
Background: The rationale of the study was to evaluate the morphological changes of chronic gastritis and its association withHelicobacter pylori infection and the efficacy of hematoxylin and eosin (H & E) and Giemsa techniques in a limited set up whichhelps in providing the vital data for subsequent treatment regimen. Materials and Methods: In this prospective study, 50 endoscopicbiopsies were obtained from dyspeptic patients from January 2016 to June 2017. The samples were fixed in 10% buffered formalinand histopathological slides were prepared using paraffin blocks and subsequently stained with routine H & E and special stainwith Giemsa. Results: There was a male preponderance in the study with a ratio of 2.3:1; the mean age of patients was 37.59 years. Ofthe 50 patients, 47 patients (94%) had chronic gastritis. Twenty-one out of 47 samples showed positivity for H. pylori with routineH & E staining, which was confirmed with the modified Giemsa staining method. Conclusion: Our study highlights the associationof H. pylori in patients with functional dyspepsia and demonstrate the importance of cost-effective Giemsa staining which can bepractically applicable in Indian set-up for the detection of H. pylori.